The defiant border - Leake, Elisabeth. (Cambridge ; New York)
xiii, [4] sayfa harita, 259 sayfa
Keywords: “The Defiant Border explores why the Afghan-Pakistan borderlands have remained largely independent of state controls from the colonial period into the twenty-first century. This book looks at local Pashtun tribes' modes for evading first British colonial, then Pakistani, governance; the ongoing border dispute between Pakistan and Afghanistan; and continuing interest in the region from Indian, US, British, and Soviet actors. It reveals active attempts first by British, then by Pakistani, agents to integrate the tribal region, ranging from development initiatives to violent suppression. The Defiant Border also considers the area's influence on relations between Pakistan, Afghanistan, and India, as well as its role in the United States' increasingly global Cold War policies. Ultimately, the book considers how a region so peripheral to major centers of power has had such an impact on political choices throughout the eras of empire, decolonization, and superpower competition, up to the so-called 'War on Terror.' One of the only historical studies of Pakistan's Pashtun tribal area (post-1947), which complements existing anthropological literature on the region and histories of the colonial era to provide readers with a fuller understanding of the region. Integrates histories of South Asia, decolonization, and the global Cold War, which provides readers with a holistic view of the region by recognizing the interconnections between international diplomacy, regional developments, subaltern movements, and colonial legacies. Considers the impact of non-state actors--Pashtun tribes--on South Asian state-building, which complements work done on state-building in India, extends understanding of the impact of peripheral areas on state power and practice, and expands understanding of the history of Pakistan.“ --